The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1109/tbcas.2016.2592525
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Reduced-Wire Interface for CMUT-Based Intravascular Ultrasound Imaging Systems

Abstract: Having intravascular ultrasound (IVUS) imaging capability on guide wires used in cardiovascular interventions may eliminate the need for separate IVUS catheters and expand the use of IVUS in a larger portion of the vasculature. High frequency capacitive micro machined ultrasonic transducer (CMUT) arrays should be integrated with interface electronics and placed on the guide wire for this purpose. Besides small size, this system-on-a-chip (SoC) front-end should connect to the back-end imaging system with a mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Hence, reducing the number of channels becomes a necessity. Analog multiplexing of the transducer channels and applying synthetic aperture imaging can reduce the number of connections to as low as two [ 65 ] with some compromise in the imaging quality and frame rate. A more efficient approach is to integrate TX beamformers and analog multiplexers with the CMUT array at the catheter tip to reduce the cable count without compromising the image quality [ 48 , 66 , 67 ].…”
Section: Integration Of Ultrasonic Transducer Arrays With Electronmentioning
confidence: 99%
“…Hence, reducing the number of channels becomes a necessity. Analog multiplexing of the transducer channels and applying synthetic aperture imaging can reduce the number of connections to as low as two [ 65 ] with some compromise in the imaging quality and frame rate. A more efficient approach is to integrate TX beamformers and analog multiplexers with the CMUT array at the catheter tip to reduce the cable count without compromising the image quality [ 48 , 66 , 67 ].…”
Section: Integration Of Ultrasonic Transducer Arrays With Electronmentioning
confidence: 99%
“…For example, a 2D array transducer with integrated ASIC in a 10 Fr catheter was developed for real-time 3D intracardiac echocardiography [31]. Especially in the development of capacitive micromachined ultrasonic transducer (CMUT), because of its MEMS/CMOS-based process, the front-end circuits or ASIC is more and more adopted and integrated [32][33][34][35][36]. However, because the frontend circuits or ASIC chips are generally developed exclusively and mainly for multi-element ultrasound transducers, and they were not easy and suitable to be used with single-element transducer.…”
Section: Introductionmentioning
confidence: 99%
“…The motivation to further develop CMUT for other application resulted from an immersion test where it has shown that CMUTs can provide a larger bandwidth over traditional piezoelectric transducers [25]. Since then CMUTs have been used in a variety of domains ranging from high-intensity focused ultrasound [26,27], ultrasound imaging [28,29,30,31,32,33], sensing application [34,35] to non-destructive testing [36]. Some of these applications and CMUT designs have been further adapted to advance CMUTs for PAI applications.…”
Section: Introductionmentioning
confidence: 99%